An Analysis on Students’ Pronunciation of a Scientific Text - Stevan Alexander Lucky; Yohanes Gatot Sutapa Yuliana; Yanti Sri Rezeki (Acitya: Journal of Teaching and Education, 2022)
This research was conducted to find out what errors the student made when reading a scientific text and the sources of those errors. The subjects of this research were 14 fourth-year-students of English Department of Teacher Training and Education Faculty of Tanjungpura University. The research methodology used in this research is Error Analysis. There were three steps that were done to find the result of this research, distribute, quantify, and analyze. The result of this research was all 14 subjects made errors when reading the text. Based on the analysis that was done during the research, it was concluded that the sources of errors occurred were intralingual and interlingual errors. Intralingual errors are errors that were made during the transfer process from L1 to TL. Interlingual errors are errors that are made because of the influence of external factors, such as L1 characteristics, slip of tongue, and habits. Keyword: Error Analysis, Scientific Text, Fourth-Year Students